Effects of Chemical upon Electron Spin Resonance (ESR) Signals in Lettuce Seeds - Eddy Noerhadi (Journal of Mathematical and Fundamental Sciences, 1968)
ESR spectrometric study of chemically treated lettuce seeds has been carried out. Solutions of HgCl2, Na2S, KOH, KCN, KBr, KF, KIO3, KIO4, KCl, KI, and K2S, as well as water and petroleum ether have been used. Germination power and respiratory activity of the same seeds have also been investigated. Boiled seeds and gamma irradiated seeds have also been studied. KI was found to be the most effective agent. Independence upon cation and pH was found. The effect of KI and KCN was found to be reversible. No correlation between respiratory activity and the number of free radicals seems to exist. Seed coat is affected first and later on the embryo is also induced by the penetrating solution.